Ritual Ratibu dalam Upacara Kematian pada Masyarakat Suku Muna di Kabupaten Muna - La Salimu . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
The purpose of this study is to know and describe the procession of the implementation of ratibu ritual on Muna tribe community. In addition, this study is also aimed to describe and interpret the meaning of symbols of objects contained in the implementation of ratibu ritual of people in Muna tribe. This study uses descriptive qualitative data, where researchers try to give an idea of the procession of the implementation of ratibu ritual and interpret the symbolic meaning of objects in the spiritual process of ratibu ritual by community of Muna tribe. The results of this study indicate: (1) The implementation of procession of ratibu ritual in Muna tribe community is carried out in three stages, namely (a) Kafongkorano ratibu (opening of the implementation of ratibu) held on the second night after the dead bodies are buried, Poratibu (implementation of the ratibu), which is performed in a special room within a mosquito net and performed for 27 times at each time of the five-day prayer. The core activity of the lebe performing the Ratibu ritual in the mosquito net is to read the sentence "Laa Ilaaha Illa Allah" 210 thousand times and read from the first night of the thousand to the fifth night after the morning prayer, (c) Kasongkono ratibu, the closing of the thousand rituals performed on the fifth night and held after the dawn prayer. The closing of the Ratibu was coupled with the slaughter of a goat as aqiqoh for the deceased/ deceased. (2) The symbolic meaning in the implementation of the Ratibu rituals of the Muna tribe society, from Kalengkano to the Ratibu, the poratibu, up to the kasibu kasibu, is generally a symbol of the limbs of the human body so arranged as a sequence of human body shape. Keywords: procession, ritual, ratibu, death, Muna Tribe